Employability Outcomes of The 13-Year Guaranteed Education Program in Sri Lanka - Mithuni Nisansala Maddumage; L.N.P. Wedikandage (Eduscape : Journal of Education Insight, 2026)
The 13-Year Guaranteed Education Program (13YGEP) in Sri Lanka offers an alternative pathway for students who do not continue to the G.C.E. Advanced Level, aiming to strengthen employability and workforce readiness. This study explores how the program supports graduates’ transition from school to employment, focusing on skill development, industry exposure, and implementation challenges.A qualitative approach was used to gather insights from key stakeholders. Data were collected from 30 graduates who completed the full program, including industrial training, as well as teachers, school principals, education administrators, and vocational education resource personnel in the Western Province in Sri Lanka. Open-ended questionnaires, semi-structured interviews, and document analysis captured participants’ experiences and perspectives.Findings show that most graduates secured employment in the private sector, engaged in self-employment, pursued overseas work, or continued further education. Practical training, workplace exposure, and soft skills particularly communication, teamwork, and problem-solving were critical for employability. Government-supported financial assistance was especially helpful for graduates pursuing self-employment. Challenges included limited technical resources, uneven industry placements, and variations in program implementation.The study concludes that the 13YGEP significantly enhances employability among school leavers, highlighting the importance of stronger industry collaboration, improved resources, and ongoing teacher development for sustainable outcomes.